From English to Indonesian: A Study of Student Approaches to Translation across Different Source Languages - Rosida, Ana; Herdi, Herdi (Utamax : Journal of Ultimate Research and Trends in Education, 2024)
This study investigates the translation practices of English Literature students, focusing on their application of theoretical frameworks in translating texts from English and Indonesian. While translation theory is typically taught in academic settings, students often deviate from the prescribed methods during practical exercises, especially when restricted to using only manual dictionaries and prohibited from utilizing electronic translation tools. Using Nida and Taber’s (1982) translation model, which includes the stages of analysis, transfer, and restructuring, this qualitative study aims to explore the translation processes employed by nine active students in an English Literature class. Data were collected through questionnaires administered to all 14 students, with nine providing valid responses. The findings show that the choice of source language significantly influenced the translation strategies used. For English texts, seven students reversed the typical sequence of translation steps, starting with transfer, followed by analysis and restructuring, while two students adhered to the traditional order. In contrast, when translating Indonesian texts, students tended to follow a more structured translation process, although one student did not complete the restructuring stage. This study not only provides valuable insights into how students engage with the translation process but also offers important implications for EFL translation instructors and researchers. Understanding how the source language affects translation practices can inform teaching strategies and enhance our approach to translation studies in the broader context of language education.